2010
DOI: 10.1111/j.1600-6143.2010.03092.x
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase 2 in Reduced‐Size Liver Transplantation: Beyond the Matrix

Abstract: †S. Padrissa-Altés and M. A. Zaouali contributed equally to this study.We studied the contribution of matrix metalloproteinase 2 (MMP2) and matrix metalloproteinase 9 (MMP9) to the beneficial effects of preconditioning (PC) in reduced-size orthotopic liver transplantation (ROLT). We also examined the role of c-Jun N-terminal kinase (JNK) and whether it regulates MMP2 in these conditions. Animals were subjected to ROLT with or without PC and pharmacological modulation, and liver tissue samples were then analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…Survival in the 60% hepatectomy and 40% SOLT groups seemed to be higher than in the 100% OLT group and this may reflect the damage induced by shear stress and portal hypertension. Our histopathological, immunohistological and biochemical findings revealed that liver damage and apoptotic induction were observed in the early postoperative period after liver surgery, as in previous studies [3,12,13,18,[29][30][31] . Paradoxically, the early postoperative period may have a therapeutic potential for a subsequent course after liver surgery.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Survival in the 60% hepatectomy and 40% SOLT groups seemed to be higher than in the 100% OLT group and this may reflect the damage induced by shear stress and portal hypertension. Our histopathological, immunohistological and biochemical findings revealed that liver damage and apoptotic induction were observed in the early postoperative period after liver surgery, as in previous studies [3,12,13,18,[29][30][31] . Paradoxically, the early postoperative period may have a therapeutic potential for a subsequent course after liver surgery.…”
Section: Discussionsupporting
confidence: 66%
“…The survival study was performed on 10 rats in each group. Cell signaling involved in proliferation, differentiation and apoptosis was confirmed at the early postoperative period after liver surgery and subsequently progressive necrosis was observed, as described previously [3,12,13,18,[29][30][31] . Serum and plasma were collected at 6 h after surgery (n = 5, in each group).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations